2020
DOI: 10.1016/j.foodhyd.2020.105737
|View full text |Cite
|
Sign up to set email alerts
|

Temperature fractionation, physicochemical and rheological analysis of psyllium seed husk heteroxylan

Abstract: Highlights: Psyllium husk heteroxylan is fractionated by a straightforward method  Fractions show distinct rheological properties  Arabinose/xylose ratio can be estimated by 2 nd -derivative FTIR and 13 C NMR spectra  Composition and spatial arrangement of sidechains are influential  Two hypotheses were proposed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 55 publications
2
39
0
Order By: Relevance
“…S6). Compositional data supporting such patterns of polymer release have been reported previously 9,10,13 , and now a model to illustrate this process, driven by polarised deposition and then expansion, is presented in Fig. 7.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…S6). Compositional data supporting such patterns of polymer release have been reported previously 9,10,13 , and now a model to illustrate this process, driven by polarised deposition and then expansion, is presented in Fig. 7.…”
Section: Discussionsupporting
confidence: 81%
“…GT61 family members have been implicated in both α-arabinosyltransferase and β-xylosyltransferase xylan backbone decoration activities in cereals 16 , 17 , Arabidopsis 18 , 19 and Plantago 20 , and copy number and type of GT61 was found to influence interspecific differences in Plantago heteroxylan fine structure 11 . The overall picture is complicated even further in that different fractions (sometimes described as layers) of P. ovata mucilage contain heteroxylans of varying substitution patterns showing that, like Arabidopsis mucilage, it is a similarly complex but orchestrated network of polysaccharides 9 , 10 , 13 . To date, many xylan synthase genes, particularly those involved in backbone decoration, are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Highly fibrillated cellulose has a large surface area, and these smaller fibrils have significantly higher interaction with psyllium heteroxylan resulting in a compact structure [ 23 ]. Psyllium husk, a rich source of soluble fiber fraction made of heteroxylan, has been shown to possess remarkable water absorption capacity and gelling properties [ 24 ]. According to them, the main functional component (F60) of psyllium husk is a complex branched heteroxylan structure that possesses unique rheological properties and offers tremendous functional applications in food industry.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of psyllium to WF at various levels (from 1 to 5%) significantly increased the water absorption (FWA) and peak time but decreased the dough stability and valorimeter values ( Table 2 ). The heteroxylans in psyllium husk have a tremendous amount of hydroxyl groups which have higher water binding capacity [ 24 ]. As expected, in the presence of 10% fine bran (FB), but with an increasing levels of psyllium husk addition, both the FWA and peak time increased significantly ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…The consensus currently suggests that the unusual b-(1?3) xylose linkages are within the side chains rather than the Plantago heteroxylan backbone (Yu et al, 2017(Yu et al, , 2018b(Yu et al, , 2019 highlighting the difficulty that researchers have in definitively describing structure. Correlations between Plantago heteroxylan side chain complexity and their unique functionalities are now being revealed and recently it was demonstrated that P. ovata heteroxylan forms 'physical' gels through side chain interlacing rather than through backbone-backbone 'junction zones', the typical mode of polysaccharide gelation (Yu et al, 2017(Yu et al, , 2018b(Yu et al, , 2019Ren et al, 2020). The unique and highly complex structure of Plantago heteroxylan is clearly integral to mucilage properties, both in situ and as a hydrocolloid ingredient, but many aspects of its synthesis, structure and biological role remain unknown.…”
Section: Plantago Seed Mucilage Composition and Propertiesmentioning
confidence: 99%